THE EFFECTIVENESS IMPLEMENTATION OF THE REGIONAL FINANCIAL MANAGEMENT INFORMATION SYSTEM CLOUD AT THE JEMBER REGENCY - Diana Sugiyantari & Purnamie Titisari (International Journal of Research Science and Management, 2018)
The increase in the volume of financial transactions of local government, demands transparency from the community, and to enhance the accountability of decentralization became the basis of the Central Government sets the Government Regulation Number 56 in 2005 about the Regional Financial Information system (SIKD). Based on PP Number 56 in 2005, the local government is obliged to convey information that is accurate, relevant financial employee administration and be accountable to the Central Government. It is encouraging local governments to use the tech no logical advances in the management of financial information. The utilization of information technology in the Finance employee administration local government in Indonesia was facilitated by the BPKP by forming a regional financial management application called Regional management information system (SIMDA). Applications continue to be developed appropriate Financial SIMDA development technology, and the last is SIMDA Financial Cloud. This paper discusses the effectiveness of the SIMDA Financial cloud at the Jember Regency using population 75 Unit Working Device Area.